2013
DOI: 10.1242/dev.095091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the zebrafish maternal and paternal transcriptomes

Abstract: Transcription is an essential component of basic cellular and developmental processes. However, early embryonic development occurs in the absence of transcription and instead relies upon maternal mRNAs and proteins deposited in the egg during oocyte maturation. Although the early zebrafish embryo is competent to transcribe exogenous DNA, factors present in the embryo maintain genomic DNA in a state that is incompatible with transcription. The cell cycles of the early embryo titrate out these factors, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
214
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(237 citation statements)
references
References 41 publications
(67 reference statements)
21
214
1
1
Order By: Relevance
“…S6B). This increase in the phenotypic severity in the F 3 generation suggests that, in the context of the notch1b-15 uq1mf/+ cross, maternal mRNA deposition is likely to help compensate for the disruption of notch1b transcription caused by deletion of the notch1b enhancer, a compensation that is reduced in a purer notch1b-15 uq1mf/uq1mf genetic background (Harvey et al, 2013). To bypass potential rescue effects of shadow enhancers or maternally deposited transcripts, we also investigated arteriovenous differentiation and sprouting angiogenesis in F 2 notch1b-15 uq1mf/uq1mf zebrafish after low-level depletion of notch1b mRNA.…”
Section: Identification Of An Arterial-specific Notch1 Intronic Enhancermentioning
confidence: 99%
“…S6B). This increase in the phenotypic severity in the F 3 generation suggests that, in the context of the notch1b-15 uq1mf/+ cross, maternal mRNA deposition is likely to help compensate for the disruption of notch1b transcription caused by deletion of the notch1b enhancer, a compensation that is reduced in a purer notch1b-15 uq1mf/uq1mf genetic background (Harvey et al, 2013). To bypass potential rescue effects of shadow enhancers or maternally deposited transcripts, we also investigated arteriovenous differentiation and sprouting angiogenesis in F 2 notch1b-15 uq1mf/uq1mf zebrafish after low-level depletion of notch1b mRNA.…”
Section: Identification Of An Arterial-specific Notch1 Intronic Enhancermentioning
confidence: 99%
“…This switch in developmental control from maternal to zygotic instructions is known as maternal-to-zygotic transition (MZT). Recent studies have provided insight into embryonic transcriptomes during MZT, identifying the earliest zygotic transcripts and revealing dynamic, highly orchestrated changes in maternal mRNA stability and translation that are important for establishment of ZGA (Thomsen et al 2010;Aanes et al 2011;Pauli et al 2012;Harvey et al 2013;Lee et al 2013;Paranjpe et al 2013;Heyn et al 2014;Subtelny et al 2014;Eichhorn et al 2016;Lim et al 2016).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Using the appearance of paternal mRNAs as a marker of zygotic transcription, this approach revealed that there is widespread post-transcriptional regulation of maternal mRNAs before zygotic transcription begins. Thus, maternal mRNAs, which are deposited in the egg during oogenesis, are held in an inactive state by proteins bound to cytoplasmic polyadenylation elements in their 3′ UTRs (Mendez and Richter, 2001;Groisman et al, 2002;Harvey et al, 2013). When required, such maternal mRNAs, including those encoding regulators of the cell cycle such as Cyclin B1 (Groisman et al, 2000(Groisman et al, , 2002, are released from their inactive state (Mendez and Richter, 2001).…”
Section: Maternal Control Of the Mztmentioning
confidence: 99%